KERANGKA PEMBERDAYAAN MASYARAKAT PEDESAAN MENUJU PEMBANGUNAN YANG BERKELANJUTAN (FRAMEWORK OF RURAL COMMUNITY EMPOWERMENT TOWARDS SUSTAINABLE DEVELOPMENT) - Subejo, Subejo; Supriyanto, Supriyanto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2005)
Rural community empowerment recently is becoming one of the central themes in the process of community development. The orientation of community development should be oriented in line and kept in pace with new approach of s sustainable development. Community empowerment process can be simplified into some strategic environmental aspects of development which covering production, economic, social and ecological issues. Rural community should be facilitated and supported in order to have enough capabilities in utilizing own and local resources in the optimum way. Steps of community empowerment process for rural community in brief are (1) identification and study on problems, potency and opportunities of rural people, (2) planning arrangement for group activities based on previous identification; (3) implementation of group activities planning; and (4) monitoring and evaluation on process and activity results continuously